2021
DOI: 10.1109/jsen.2021.3104967
|View full text |Cite
|
Sign up to set email alerts
|

Image Reconstruction of Electrical Impedance Tomography Based on Optical Image-Guided Group Sparsity

Abstract: The low spatial resolution of Electrical Impedance Tomography (EIT) makes it challenging to conduct quantitative analysis of the electrical properties of imaging targets in biomedical applications. We in this paper propose to integrate optical imaging into EIT to improve EIT image quality and report a dual-modal image reconstruction algorithm based on optical image-guided group sparsity (IGGS). IGGS receives an RGB microscopic image and EIT measurements as inputs, extracts the structural features of conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For instance, Gong et al proposed to incorporate structural information from CT or preliminary EIT reconstructions into the EIT inversion process using group lasso [22]. Liu et al reported a group lasso based dual-modal reconstruction method and their grouping method is based on the semantic segmentation of the prior image [23]. The segmentation algorithm needs to be carefully chosen and tuned for a specific application, and its complexity is even higher than the reconstruction algorithm in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gong et al proposed to incorporate structural information from CT or preliminary EIT reconstructions into the EIT inversion process using group lasso [22]. Liu et al reported a group lasso based dual-modal reconstruction method and their grouping method is based on the semantic segmentation of the prior image [23]. The segmentation algorithm needs to be carefully chosen and tuned for a specific application, and its complexity is even higher than the reconstruction algorithm in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…With L 2 -norm as the penalty term, Tikhonov regularization method has been widely used due to its advantages of simple and fast implementation. However, this method fails to maintain sharp edge information, and over-smoothness is observed in the reconstructed images (Liu and Yang, 2021). Thus, the reconstruction quality of this method needs improvement.…”
Section: Image Reconstruction Based On the Proposed Methodsmentioning
confidence: 99%
“…With boundary data measured, conductivity distribution inside the detected object can be reconstructed via image reconstruction. [6][7][8] At present, EIT has become one of the fastest-developing electrical tomography techniques and shows great potential in various medical imaging fields, such as brain imaging, pulmonary monitoring, and breast cancer detection. [9][10][11] In EIT, a variety of studies have been conducted, such as quantization error and electrode position errors in the modeling.…”
Section: Introductionmentioning
confidence: 99%